Faktor Yang Berhubungan Dengan Pola Konsumsi Pada Ibu Hamil - Endah Mulyani (IJMT : Indonesian Journal of Midwifery Today, 2022)
Consumption pattern is defined as the composition of the type and amount of food consumed by individuals or groups of people at a certain time. The fulfillment of the diversity of foods consumed by pregnant women is an important key in the nutritional status of pregnant women. Given that nutritional status is associated with maternal morbidity and mortality. The purpose of this study was to analyze the relationship between education level, employment status, income level and knowledge of balanced nutrition with consumption patterns of pregnant women in Leran Gresik village. This type of analytic research with a cross sectional approach. The research sample was 54 pregnant women in the village of Leran Gresik who were selected by purposive sampling technique. Data collection was done by interview technique using a questionnaire. Data analysis using chi square test. The results of this study indicate that the level of knowledge and level of income is related to the consumption pattern of pregnant women with p value ≤ 0.05 and there is no relationship between employment status and education level with consumption patterns of pregnant women, which is equal to p ≥ 0.05. Pregnant women should pay attention to the food they eat so that the health of the mother and child is optimal.